Penyuluhan Kesadaran Hukum sebagai Pilar Implementasi Peraturan Perundang Undangan di Masyarakat Desa - Lisda Apriliani Sobirin; Taufik Taufik; Muhamad Iqbal Ansori Firdaus; Ilman Napiah; Mardiman Mardiman (Universitas Methodist Indonesia, 2026)
Low legal literacy in rural communities often hinders the effective implementation of legislation at the local level, potentially triggering disputes and reducing public compliance. This community service activity aims to enhance legal awareness among residents of Wantilan Village as a strategic pillar for regulatory enforcement. The method employed integrates Community-Based Research (CBR) and Participatory Action Research (PAR), encompassing interactive seminars, participatory discussions, and free legal consultation services. Program effectiveness was evaluated using pretest and posttest instruments administered to 85 participants. Results indicate a significant increase in legal awareness scores from an average of 42.5 to 78.3 (p < 0.01), with the highest improvement in knowledge of rights/obligations and compliance attitudes. A total of 24 consultation cases were successfully handled, primarily focusing on civil and village administration matters in a preventive manner. The findings confirm that a participatory educational approach effectively bridges the gap between formal legal norms and community practices. It is concluded that the program successfully strengthened the community’s legal awareness foundation. It is recommended that this model be developed into a sustainable village legal clinic integrated with village government programs and partner universities.